School readiness analysis in implementing differentiated learning in Kurikulum Merdeka - Sisworo Hadi; Dinn Wahyudin (Himpunan Pengembang Kurikulum Indonesia (HIPKIN), 2024)
The principle of differentiated learning is fundamental to the implementation of the Merdeka curriculum. Organizational readiness analysis became crucial before the implementation of differentiated instruction. This research aims to determine the school's readiness as an institution or organization to implement Differentiated Learning in Kurikulum Merdeka. This research was conducted at SMP Penggerak in Bogor City. The research is quantitative research with a survey method. The level of school readiness will be measured using the Readiness Framework Thinking Tool from Scaccia et al. R=MC2 readiness framework is the framework for the instrument adopted. (R: Readiness; C: Innovation Specific Capacity; C: General Capacity). Based on research on School Readiness Levels), the percentage of readiness levels for the three elements of readiness levels is 80.1 percent for motivation elements, 83.7 percent for general capacity elements, and 87.4 percent for particular capacity elements. Using an Interactive System Framework (ISF) and Quality Implementation Framework (QIF), the implementation is divided into 4 phases. In phase 1, all processes are related to internal preparation. In phase 2, schools can develop teams under learning committees. In phase 3, the development of a sustainable strategy, and in phase 4, it is necessary to develop a pattern for the future. AbstrakPrinsip pembelajaran berdiferensiasi menjadi sangat penting pada implementasi kurikulum merdeka. Sebelum implementasi sebuah inovasi seperti pembelajaran berdiferensiasi, sangat perlu dilakukan analisis bagaimana tingkat kesiapan sekolah untuk mengimplementasikan pembelajaran berdiferensiasi. Tujuan penelitian ini untuk mengetahui kesiapan sekolah sebagai lembaga atau organisasi dalam menerapkan Pembelajaran Diferensiasi di Kurikulum Merdeka. Penelitian ini menganalisis kesiapan SMP Penggerak di Kota Bogor dalam menerapkan pembelajaran Diferensiasi. Penelitian ini merupakan penelitian kuantitatif dengan metode survei. Tingkat kesiapan sekolah akan diukur dengan menggunakan Readiness Framework Thinking Tool dari Scaccia, et. Kerangka kesiapan R=MC2 merupakan kerangka instrumen yang diadopsi. (R: Kesiapan; C: Kapasitas Khusus Inovasi; C: Kapasitas Umum). Berdasarkan hasil penelitian Tingkat Kesiapan Sekolah), persentase tingkat kesiapan ketiga unsur tingkat kesiapan adalah 80,1 persen unsur motivasi, 83,7 persen unsur kapasitas umum, dan 87,4 persen unsur kapasitas khusus. Dengan menggunakan Interactive System Framework (ISF) dan Quality Implementation Framework (QIF), proses pelaksanaan pembelajaran berdiferensiasi di SMP Penggerak Kota Bogor dapat dibagi menjadi 4 tahap. Pada tahap 1 semua proses yang berkaitan dengan persiapan internal harus dilakukan. Pada fase 2, sekolah dapat mengembangkan tim di bawah komite pembelajaran. Pada fase 3 pengembangan strategi berkelanjutan dan pada fase 4 perlu dikembangkan pola implementasi untuk masa depan.Kata Kunci: kurikulum merdeka; pembelajaran berdiferensiasi; SMP penggerak